Bonds Transaction Services and the Term Structure of Interest Rates: Implications for Equilibrium Determinacy - Massimiliano Marzo; Paolo Zagaglia (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
Bonds Transaction Services and the Term Structure of Interest Rates: Implications for Equilibrium Determinacy Abstract: We introduce two bonds in a standard New-Keynesian model to study the role of segmentation in bond markets for the determinacy of rational expectations equilibria. We use a strongly-separable utility function to model short-term bonds providing transaction services for the purchase of consumption goods. Long-term bonds, instead, provide the standard services of store of value. We obtain a fully analytical solution for the bond pricing kernel, allowing to endogenize the term spread within the model. In this way, we study equilibrium determinacy properties within a context embedding the full information derived from term structure of interest rates. Our results show that, when utility is weakly separable between consumption and bonds, the Taylor principle holds only conditional to a non-linear relation between output and inflation targeting coefficients of monetary policy rule. Achieving solution determinacy requires to constraint policy coefficients to lie within bounds depending on structural parameters of the model. This paper provides an analytical setting useful for several generalizations to address the stability properties in dynamic models including the term structure of interest rates, induced by policy rules.
Keywords: E43; E63; 330